Investigating the role of ADAM10 and ADAM17 in cetuximab resistance in head and neck squamous cell carcinoma - Kareemaghay, S (2014)
Epithermal Growth Factor Receptor (EGFR) is overexpressed in up to 90% of head and neck squamous cell carcinoma (HNSCC). Cetuximab is the first and the only anti-EGFR monoclonal antibody which received approval from FDA for the treatment of HNSCC. However, most patients either do not respond to cetuximab or develop acquired resistance. The aim of my D.Phil. study was to investigate the role of ADAM10 and 17 in resistance mechanisms of cetuximab in HNSCC. Chronic exposure to cetuximab led to an activation of HER receptors and downstream signalling pathways in HNSCC cell lines. Higher levels of ADAM10 and 17 and their substrates, BTC and NRG-1 were found in cetuximab resistant cells compared to their parental cells, suggesting the involvement of ADAM-mediated ligands’ release in reactivation of HER receptors. Inhibition or knockdown of ADAM10 and 17 enhanced cetuximab response and reversed cetuximab resistance in HNSCC cells. In addition, results from this study showed that the combination of cetuximab with EGFR-TKIs had greater effect in parental cells and reversed cetuximab resistance in HNSCC cells. Upregulation of ADAM10 and 17 also was observed in HNSCC TMAs compared to normal head and neck TMAs. High nuclear ADAM10 and cytoplasmic ADAM17 expression levels were associated with shorter DFS. By evaluating tumour excision samples from HNSCC patients who underwent a cetuximab window study high ADAM10 and 17 expression levels were found to be associated with poor response to cetuximab. In conclusion cetuximab-induced ADAM-mediated ligands’ release is a potential mechanism of resistance to cetuximab in HNSCC. Thus, targeting ADAM10/17 or subsequent HER activations may represent an important strategy in overcoming resistance to cetuximab in HNSCC. Results from this study also suggest the implication of ADAM10 and 17 as potential prognostic and predictive biomarkers in HNSCC although further validation is required.